Analisis Faktor-Faktor yang Mempengaruhi Ketimpangan Pendapatan Antar Daerah Kabupaten/Kota di Provinsi Daerah Istimewa Yogyakarta Tahun 2010-2018 - Dika Hasto Muhammad Afif (Universitas Diponegoro, 2022)
The high level of income inequality in D.I Yogyakarta shows the existence of uneven economic development. This study aims to analyze the effect of per capita GRDP, total population, and general allocation funds in the Special Region of Yogyakarta. This study uses a fixed effect model (FEM) analysis method with secondary data in the form of panel data consisting of cross-sectional data from 5 districts/cities and time-series data from 2010 to 2018. The data is processed with Eviews 10. The results of the study indicate that the GRDP per capita variable has a significant effect on income inequality in D.I Yogyakarta. Meanwhile, the variables of Population and General Allocation Funds show insignificant results on the level of income inequality in D.I Yogyakarta